Computational Thinking in Elementary School Students: A Bibliometric Review - Maharani, Swasti; Yuniahastuti, Irna Tri; Prastyaningrum, Ihtiari; Susanti, Vera Dewi; Romandoni, Hendrisa Rizqie (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This study aims to provide an in-depth overview of trends in Computational Thinking (CT) learning among elementary school students through bibliometric analysis. The development of CT skills, which include logical thinking, systematic problem-solving, decomposition, pattern recognition, abstraction, and algorithmic design, is essential to prepare students for navigating a technology-driven future. By encouraging CT in primary education, students better understand technology and versatile skills that can be applied in various fields. This study uses a bibliometric approach by systematically collecting and analyzing scientific articles on CT in elementary schools. The analysis used specific metrics, including publication trends, citation analysis, and identifying leading research areas. Data is drawn from leading academic databases and analyzed to track the progress and impact of CT research over time. The results show a significant increase in publications and citations on CT, which peaked in 2021. The main trend highlights the importance of visual programming tools like Scratch in improving students' understanding of programming concepts, logic, and motivation. The study also uncovered research gaps and suggested areas that need further investigation, particularly in developing CT curricula and more effective teaching methodologies. These findings are expected to significantly contribute to advancing CT education and help equip the younger generation with the skills needed.